QUALITY PRACTICE OF FUTURE PRIMARY CLASS TEACHERS - A FACTOR OF PEDAGOGICAL SKILLS (CAHIERS MAGELLANES-NS, 2024)
In the field of education, which is currently developing at a rapid pace, the task of forming comprehensive professional competencies of graduates of modern higher education is set before them, and the higher educational institutions of our country are interested in training competitive specialists who are in demand in the modern labor market. . University graduates, future experts in their field, during their studies, not only acquire the knowledge, skills and qualifications necessary for successful self-realization in the professional field, but also develop new professionally important qualities and, in this regard, have to work on z. In order to achieve this goal, a whole set of pedagogical tools is used, including in the training of students, in which the qualities corresponding to the qualification requirements are mastered by those who are trained. Organization of such a system of professional training of future elementary school teachers helps to form professional competence, that is, pedagogical competence in students.